The current state of secondary school teachers’ morale competence to teach - Nigatu Benti; Wudu Tarekegne (Cogent Education, 2022)
AbstractThe purpose of this study was to assess teachers’ morale competence in the secondary school of Kersa woreda. To achieve this objective, the researchers used a cross-sectional survey research design. The study was carried out on 110 secondary school teachers who were teaching grade nine. A questionnaire and an interview were used to collect data. The analysis of quantitative data was carried out by using descriptive statistics, whereas the qualitative data was analyzed with narrations to substantiate the quantitative findings. Based on the findings, the study recommended that to improve teachers’ morale, Woreda education office, secondary school principals, vice-principals, and secondary school supervisors should give special attention to encouraging teachers’ morale competence by providing fair and equitable school facilities and services system and creating awareness in the community to support education to achieve school goals and objectives.